2001
DOI: 10.1074/jbc.m006809200
|View full text |Cite
|
Sign up to set email alerts
|

Subcytotoxic H2O2 Stress Triggers a Release of Transforming Growth Factor-β1, Which Induces Biomarkers of Cellular Senescence of Human Diploid Fibroblasts

Abstract: Stress-induced premature senescence (SIPS) is induced 3 days after exposure of human diploid fibroblasts to subcytotoxic oxidative stress with H 2 O 2 , with appearance of several biomarkers of replicative senescence. In this work, we show that transforming growth factor-␤1 (TGF-␤1) regulates the induction of several of these biomarkers in SIPS: cellular morphology, senescence-associated ␤-galactosidase activity, increase in the steady-state level of fibronectin, apolipoprotein J, osteonectin, and SM22 mRNA. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
229
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(250 citation statements)
references
References 22 publications
16
229
1
4
Order By: Relevance
“…At 750 mJ/cm 2 , this proportion increased by more than three-fold. Similar results were obtained when foetal lung HDFs were exposed to subcytotoxic concentrations of H 2 O 2 [15] or t-BHP [10]. According to this criteria, skin HDFs exposed to UVB and foetal lung HDFs exposed to H 2 O 2 or to t-BHP behave like presenescent cells.…”
Section: Discussionsupporting
confidence: 75%
“…At 750 mJ/cm 2 , this proportion increased by more than three-fold. Similar results were obtained when foetal lung HDFs were exposed to subcytotoxic concentrations of H 2 O 2 [15] or t-BHP [10]. According to this criteria, skin HDFs exposed to UVB and foetal lung HDFs exposed to H 2 O 2 or to t-BHP behave like presenescent cells.…”
Section: Discussionsupporting
confidence: 75%
“…We have previously shown that treatment with 150 Amol/L H 2 O 2 for 2 hours is sufficient to promote premature senescence in NIH 3T3 cells 7 to 10 days after oxidative stress (33). It is also well known that senescent cells display a typical large and flat morphology (41)(42)(43). Thus, we evaluated the cell morphology of NIH 3T3 cells treated with subcytotoxic levels of hydrogen peroxide in the presence or absence of p38 MAPK inhibitor 7 days after oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Acid h-galactosidase activity (at pH 6) is a well-established biochemical marker that is associated with the senescent cell phenotype (41)(42)(43). A representative field is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress has been shown to induce stress-induced premature senescence in fibroblasts (Dasari et al, 2006;Frippiat et al, 2001). Senescent cells show different features from proliferative cells.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been shown to induce stress-induced premature senescence in fibroblasts (Dasari et al, 2006;Frippiat et al, 2001). Stress-induced premature senescence was recently invoked as an explanation of irreversible growth arrest characterized by senescence-specific cell morphology and gene expression, similar to the phenomenon of replicative senescence (Touissant et al, 2000).…”
Section: Introductionmentioning
confidence: 99%